2009
DOI: 10.1007/s00348-009-0711-9
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric three-component velocimetry measurements of the turbulent flow around a Rushton turbine

Abstract: Volumetric 3-component velocimetry measurements have been taken of the flow field near a Rushton turbine in a stirred tank reactor. This highly unsteady, three-dimensional flowfield is characterized by a strong radial jet, large tank-scale ring vortices, and small-scale blade tip vortices. Approximately 15,000 3d vectors were obtained in a cubic volume; these data offer the most comprehensive view to date of this flow field, especially since they are acquired at three Reynolds numbers (15,000, 107,000, and 137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
5
14
1
Order By: Relevance
“…8 shows that the trailing vortices can be detected in a range up to 100 o . This is in an agreement with results of Sharp et al [26] who observed the trailing vortices beyond blade passage up to approximately 140 o . A comparison of our data with data of Sharp et al [26] is made in Fig.…”
Section: Identification Of the Trailing Vorticessupporting
confidence: 93%
See 4 more Smart Citations
“…8 shows that the trailing vortices can be detected in a range up to 100 o . This is in an agreement with results of Sharp et al [26] who observed the trailing vortices beyond blade passage up to approximately 140 o . A comparison of our data with data of Sharp et al [26] is made in Fig.…”
Section: Identification Of the Trailing Vorticessupporting
confidence: 93%
“…A lot of areas which are evidently not related to the vortical structures of the trailing vortices can be seen. This is in relation with conclusions given by Sharp et al [26]. To overcome such inconsistencies we propose to use a threshold value of λ 2 which could remove these undesirable areas.…”
Section: Identification Of the Trailing Vorticessupporting
confidence: 64%
See 3 more Smart Citations